2000
DOI: 10.2337/diabetes.49.2.293
|View full text |Cite
|
Sign up to set email alerts
|

Leptin induces direct vasodilation through distinct endothelial mechanisms.

Abstract: In this study, we reveal that leptin evokes an acute hypotensive effect in 6-hydroxydopamine sympathectomized rats (response to maximal leptin dose, mean blood pressure: from 92 +/- 4 to 78 +/- 2 mmHg, P < 0.01). This hemodynamic effect is related to a direct action of the hormone on vascular tone, since in aortic and mesenteric rings increasing doses of leptin evoke a dose-dependent vasorelaxation (aorta: from 3 +/- 1 to 36 +/- 3, n = 15; mesenteric: from 6 +/- 1 to 30 +/- 5, n = 10), which is impaired by end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
274
3
11

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 308 publications
(302 citation statements)
references
References 12 publications
14
274
3
11
Order By: Relevance
“…Since leptin's positive [18][19][20] and negative 14,15 influences on vascular function has been reported, partial correlations were performed while adjusting for age to determine if leptin is associated with the obese African group's possible decreased vascular function, or the obese Caucasian group's possible normal or enhanced vascular function. By doing so, leptin failed to show any associations with the vascular profile in the obese African group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since leptin's positive [18][19][20] and negative 14,15 influences on vascular function has been reported, partial correlations were performed while adjusting for age to determine if leptin is associated with the obese African group's possible decreased vascular function, or the obese Caucasian group's possible normal or enhanced vascular function. By doing so, leptin failed to show any associations with the vascular profile in the obese African group.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, leptin correlated negatively with TPR and positively with C W , implicating leptin as a possible role player in the accommodating effect observed in the obese Caucasian group, but not in the obese African group. One may speculate that this accommodating effect could be the result of leptin's angiogenic 37,38 and/or vasodilatory [18][19][20] effect, which would lead to decreased TPR and increase C W .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…32 In obese 7-11-year-old children, no association was found between leptin and energy, fat or carbohydrate intake. 33 Intravenous leptin in animals increases sympathetic nerve activation 34 and produces endothelium-dependent vasodilation, 35 resulting in variable effects on BP. Although several adult studies have found increased leptin concentrations are correlated with hypertension, 5 other studies have not.…”
Section: Hypertension Insulin Resistance Resistin and Adiponectinmentioning
confidence: 99%